Evaluating a Board Game Designed to Promote Young Children’s Delay of Gratification - Anzman-Frasca, Stephanie; Singh, Anita; Curry, Derek; Tauriello, Sara; Epstein, Leonard H.; Faith, Myles S.; Reardon, Kaley; Pape, Dave (Frontiers in Psychology, 2020)
Objective: Delay of gratification, or the extent to which one can resist the temptation of an immediate reward and wait for a larger reward later, is a self-regulatory skill that predicts positive outcomes. The aim of this research was to conduct initial tests of the effects of a board game designed to increase children’s delay of gratification via two experimental studies. Methods: Preschool children were randomized to play the study game or a control game. In Study 1, there were 48 children in the analytic sample, with a mean age of 4.81 + 0.55 years; Study 2 included 50 children (M=4.02 + 0.76 years). Delay of gratification was assessed during the study game, as well as before and after game play sessions using the Marshmallow Test. Results: In both studies, the intervention group’s likelihood of delaying gratification during the study game increased across game-play sessions (p<.05). In Study 1, the intervention group also increased wait times during the Marshmallow Test versus controls (p=0.047). In Study 2, there was no effect on Marshmallow Test wait times. . Conclusion: Results provide some initial evidence supporting potential efficacy of a board game designed to increase delay of gratification. Future research can clarify: 1) which components of game play (if any) are linked with broader changes in delay of gratification, 2) impacts of this intervention in more diverse samples, and 3) whether experimental manipulation of delay of gratification affects outcomes like achievement and weight, which have been linked to this skill in observational studies.